(untitled) (Rudarsko-geološko-naftni zbornik, 2016)
Asteroids are the largest minor bodies in the Solar System. Nowadays they are in the research focus due to several facts about them: first, a subclass of asteroids can collide with Earth, and consequences of such a collision are dramatic. Second, they are now seen as source of materials that are becoming scarce on Earth, and they will be needed in future space constructions anyway. Third, they are holding clues about the origin and evolution of the Solar System. In this article, a short overview of current knowledge about asteroids is presented. Last, but not least, as several Croatian scientists were recently honored by naming an asteroid after them, a short overview of the naming process is given.